2023
DOI: 10.1039/d2fo03672j
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the mechanism by which oyster peptides target IL-2 in melanoma cell apoptosis based on RNA-seq and m6A-seq

Abstract: Melanoma is a kind of skin cancer with high malignancy and strong proliferation and invasion abilities. Chemotherapy drugs in the clinic have the disadvantages of high price and high toxicity....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…The results of this analysis revealed that Kaempferol has a mass (286), number of hydrogen bond donors (4), number of hydrogen bond acceptors (6), log P (2.305), and molar reactivity (72.385). These characteristics provide information on the physicochemical properties of Kaempferol, which are important in the evaluation of the pharmacokinetic potential and availability of the drug in potential clinical applications [48][49][50]. Table 2 presents the data from Lipinski and Figure 2 depicts the results of the Tyr and 3awu interactions.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this analysis revealed that Kaempferol has a mass (286), number of hydrogen bond donors (4), number of hydrogen bond acceptors (6), log P (2.305), and molar reactivity (72.385). These characteristics provide information on the physicochemical properties of Kaempferol, which are important in the evaluation of the pharmacokinetic potential and availability of the drug in potential clinical applications [48][49][50]. Table 2 presents the data from Lipinski and Figure 2 depicts the results of the Tyr and 3awu interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, these findings strengthen the argument that Masilinic Acid can interact with the CD81 antigen and potentially inhibit the HIV infection process. [31][32][33][34] Figure 1 shows the visualization results of Masilinic Acid and the CD81 antigen in Protein Plus.…”
Section: Resultsmentioning
confidence: 99%
“…In PyMol, these components can be removed to purify the protein. [30][31][32] Furthermore, proteins sometimes have more than one conformation or chain. In this scenario, the researcher needs to select which conformation or chain is most relevant to their docking study.…”
Section: Resultsmentioning
confidence: 99%